2017
DOI: 10.3847/1538-4357/aa63ee
|View full text |Cite
|
Sign up to set email alerts
|

The Photodissociation of HCN and HNC: Effects on the HNC/HCN Abundance Ratio in the Interstellar Medium

Abstract: The impact of the photodissociation of HCN and HNC isomers is analyzed in different astrophysical environments. For this purpose, the individual photodissociation cross section of HCN and HNC isomers have been calculated in the 7-13.6 eV photon energy range for a temperature of 10 K. These calculations are based on the calculation of three-dimensional adiabatic potential energy surfaces of the 21 lower electronic states. The cross sections are then obtained using a quantum wave packet calculation of the rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…There exists no dependence of the HNC/HCN ratio on the type or presence of an X-ray source. For the HNC/HCN line ratio to decrease steadily with UV luminosity, high energy photons must be either heating the gas within the PDR or selectively photodissociating HNC (Aguado et al 2017). Under the former scenario, as CSPN UV luminosity rises, the resulting CSPN-induced ionization evidently raises the local temperature to exceed the activation energy for conversion of HNC into HCN+H.…”
Section: Hnc/hcn Ratio With Cspn L Uvmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists no dependence of the HNC/HCN ratio on the type or presence of an X-ray source. For the HNC/HCN line ratio to decrease steadily with UV luminosity, high energy photons must be either heating the gas within the PDR or selectively photodissociating HNC (Aguado et al 2017). Under the former scenario, as CSPN UV luminosity rises, the resulting CSPN-induced ionization evidently raises the local temperature to exceed the activation energy for conversion of HNC into HCN+H.…”
Section: Hnc/hcn Ratio With Cspn L Uvmentioning
confidence: 99%
“…Another potential mechanism that might drive the HNC/HCN ratio is the difference in photodissociation rates of HNC and HCN. Calculations by Aguado et al (2017), taking into account the photodissociation cross sections of each molecule as well as variation in the incident UV radiation field, find that selective photodissociation can increase the rate of destruction of HNC by a factor of ∼2-10 relative to that of HCN. While high effective temperature sources, such as CSPNe, have fewer lowenergy photons and thus a smaller effect on photodissociation rates than cool sources, the interaction between the strength of the evolving UV source and the photochemical reaction rates of HNC and HCN could be sufficient to drive the observed trend.…”
Section: Hnc/hcn Ratio With Cspn L Uvmentioning
confidence: 99%
“…As we mentioned above, there are at least two effects discussed for reducing the [HNC]/ [HCN] ratio (Hirota et al 1998;Colzi et al 2018;Aguado et al 2017 (2018) estimated the dimensionless FUV strength G 0 from the Herschel 70 µm data and they found that the G 0 parameter of the FIR 4 region exceeds 100 and peaked at around FIR 3 (∼ 7000) and…”
Section: N 2 H + and Ccs Abundancesmentioning
confidence: 99%
“…The photoelectron spectrum of HNC isomer is calculated using a wave-packet method similarly to that applied to calculate the photodissociation of HCN42,43 and photodetachment of OHF – . 39 In the present approach, the transition dipole moment is neglected, and the initial wave-packet is the rovibrational wave function of the neutral HNC isomer.…”
Section: Methodsmentioning
confidence: 99%